To study the design of hybrid circuit breaker (HCB) for domestic installation: to design earth leakage circuit breaker incorporating overvoltage protection / Abdul Rahim Ibrahim - Ibrahim, Abdul Rahim (1997)
The propose HCB is a combination of conventional Earth Leakage Circuit Breaker (ELCB) and some power electronics devices to provide better protection to user and their appliances. ELCB is a protective device commonly used in domestic homes. It protects human life against the incident of any leakage current to ground, by breaking (tripping) the electrical system, In the case of overvoltage, ELCB cannot detect and as a result of a long duration overvoltage some electrical appliances are bound to feil. Therefore the objective of this project is to design a hybrid circuit breaker or 'HCB' so it can detect both, earth leakage current and overvoltage as well. At the end of the project, it is hope that this device could be further studied, developed and produced / manufactured so that it can help mankind to protect human lives and their properties.